2011
DOI: 10.1007/s12098-011-0655-y
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Serum Cystatin-C for Full-Term and Preterm Neonates in Istanbul

Abstract: Evaluation of cystatin C can be effective for follow-up of renal pathologies, because it is not affected by gender, body weight and muscle mass and has a constant production rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 19 publications
11
11
0
Order By: Relevance
“… used the PENIA method in 100 normal term neonates and also measured higher values of cysC in cord blood (median 2.02 mg/L; range 1.54 to 2.64), which are close to our preliminarily published results . Somewhat lower values than ours were reported by Dorum (1.21 ± 0.31 mg/L), who measured cysC values in cord blood in 33 normal term neonates taken just above the insertion point at which the umbilical cord attaches to the placenta, where the possibility of mixture with the mother's blood is higher.…”
Section: Discussionsupporting
confidence: 89%
“… used the PENIA method in 100 normal term neonates and also measured higher values of cysC in cord blood (median 2.02 mg/L; range 1.54 to 2.64), which are close to our preliminarily published results . Somewhat lower values than ours were reported by Dorum (1.21 ± 0.31 mg/L), who measured cysC values in cord blood in 33 normal term neonates taken just above the insertion point at which the umbilical cord attaches to the placenta, where the possibility of mixture with the mother's blood is higher.…”
Section: Discussionsupporting
confidence: 89%
“…But in Dorum's research, 26 Cys-C values showed a downward trend as follows (P < 0.05): 1.41 AE 0.27 mg/L (28-33 weeks), 1.22 AE 0.30 mg/L (33-36 weeks) and 1.21 AE 0.31 mg/L (>37 weeks), respectively. But in Dorum's research, 26 Cys-C values showed a downward trend as follows (P < 0.05): 1.41 AE 0.27 mg/L (28-33 weeks), 1.22 AE 0.30 mg/L (33-36 weeks) and 1.21 AE 0.31 mg/L (>37 weeks), respectively.…”
Section: Discussionmentioning
confidence: 83%
“…Even if we limit the analysis to blood samples in healthy term neonates in the first 24 h of life to restrict the impact of covariates, there is significant difference in mean values reported following PETIA [16,19,20] or ELISA [26] compared to PENIA assays [21,23,27,28,30], as illustrated in Figure 1. Finally, (iv) disease characteristics like respiratory distress [36], bilateral kidney abnormalities [25], peripartal asphyxia [30,38], aminoglycoside exposure [29], hemoglobin [30,38], renal dysfunction [33,37] or sepsis [39] also affect the CysC values observed, but not always in the expected direction.…”
Section: Discussion: How To Aim For a Moving Target?mentioning
confidence: 99%
“…In 5 of these cohorts, CysC measurement was based on PENIA [21,23,27,28,30], there was one ELISA measurement [26] and 3 PETIA [16,19,20] based measurements. Mean values following PENIA were significantly lower when compared to non-PENIA techniques [PENIA = particle enhanced nephelometric immune-assay; PETIA = particle enhanced turbimetric immune-assay; ELISA = enzyme linked immune-sorbent assay].…”
Section: Figurementioning
confidence: 99%